(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.4059.159-186 The aim of this study is to analyze the characteristics of academic and professional experience that have contributed to the participation on the Boards of Directors of Brazilian joint stock companies, in light of human capital theory. The study examined the gender composition of 410 companies listed in 2011 on the BM&FBovespa and the resumes of 158 directors who compose it, using the technique of content analysis. The results showed that 7.3% of seats in the boards are held by women. The analysis of the curriculum vitae showed that most of these women are graduated, they have diverse professional backgrounds and many have previous experience as board directors in other companies. Despite the investment in human capital held by these women, the main reason for referral to a seat on the Brazilian boards is the family ties, representing 40% of the total.